2007
DOI: 10.1160/vcot-06-12-0093
|View full text |Cite
|
Sign up to set email alerts
|

Tibial segmental bone defect treated with bone plate and cage filled with either xenogeneic composite or autologous cortical bone graft

Abstract: Tibia segmental defect healing in sheep were clinically, radiographically and histologically evaluated. Twelve young sheep aged four to five months were divided into two groups, G1 and G2. A 3.5 cm long segmental defect was created in the right tibial diaphysis with maintenance of the periosteum. The bone defects in both groups were stabilized with a bone plate combined with a titanium cage. In G1 the cage was filled with pieces of autologous cortical bone graft. In G2 it was filled with a composite biomateria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…Besides artificial fracture models and osteotomies with and without defined gap sizes for examination of common fracture healing, studies could also be found where critical size defects in the sheep model are examined . The defect size varied between 10 mm and 50 mm and the tibia was used in all cases but one.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides artificial fracture models and osteotomies with and without defined gap sizes for examination of common fracture healing, studies could also be found where critical size defects in the sheep model are examined . The defect size varied between 10 mm and 50 mm and the tibia was used in all cases but one.…”
Section: Animal Modelsmentioning
confidence: 99%
“…134,135 Besides artificial fracture models and osteotomies with and without defined gap sizes for examination of common fracture healing, studies could also be found where critical size defects in the sheep model are examined. [136][137][138][139][140][141] The defect size varied between 10 mm and 50 mm and the tibia was used in all cases but one. In general, plating is the predominant fixation method for these critical size defects, although different plating systems are described.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Several orthopaedic studies have used sheep as an experimental model to test materials or surgical procedures for use on human beings, such as replacement or reconstruction of the cranial cruciate ligament (10)(11)(12) and the treatment of fractures and segmental bone defects using bone plates (13)(14)(15)(16) and external fixators (17,18). However, the influence of the bone axial alignment and joint orientation on the support of bodyweight loads during locomotion is possibly a predisposing factor for osteoarthritis development or implant failure, and have not been evaluated in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…At 60 and 90 days callus remodelling occurred. Histological and morphometric analysis 90 days post surgery showed that the quantity of implanted materials still present were similar for both groups while the quantity of newly formed bone was less (p = 0.0048) in the cortical bone graft group occupying 51 ± 3.46% and 62 ± 6.26% of the cage space, respectively (Teixeira et al 2007 ) .…”
Section: Sheep and Goatsmentioning
confidence: 90%